An integral molded inductor containing an iron-based nanocrystalline alloy powder and a method of making the same

CN122575967BActive Publication Date: 2026-10-16ZHONGSHAN SKCOIL ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611000426.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-16
Estimated Expiration
2046-07-07

AI Technical Summary

Technical Problem

[0005]本公开的目的在于提供一种含铁基纳米晶合金粉末的一体成型电感及其制备方法,解决现有一体成型电感用铁基粉难以兼顾低高频损耗和耐腐蚀性的问题

Benefits of technology

在本公开的一些实施例所提供的技术方案中,一方面,由于采用了将铁基合金熔炼并卷绕形成卷绕磁芯,再对卷绕磁芯进行真空退火以促进α-Fe纳米晶均匀析出的技术手段,解决了现有一体成型电感直接采用纯铁粉或常规铁合金粉时,磁粉内部软磁组织不够均匀、磁导率与高频损耗难以兼顾的问题,从而使晶化处理带材内部形成均匀析出的α-Fe纳米晶结构,达到了提高铁基磁粉软磁性能稳定性、改善磁导率并降低后续高频损耗基础的技术效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122575967B_ABST
    Figure CN122575967B_ABST
Patent Text Reader

Abstract

The present disclosure relates to the field of electronic materials, and provides an integrated inductor containing iron-based nanocrystalline alloy powder and a preparation method thereof. The method comprises the following steps: melting and winding an iron-based alloy to form a wound magnetic core, vacuum annealing the wound magnetic core to promote uniform precipitation of alpha-Fe nanocrystals, obtaining a crystallization treatment strip, crushing and ball milling the crystallization treatment strip, obtaining a ball milled powder after ball milling for a preset time, adding the ball milled powder into a phosphate passivation solution for surface treatment, obtaining phosphated magnetic powder, mixing and granulating the phosphated magnetic powder with a modified component, hot pressing to form an inductor green body, and then performing solidification treatment to obtain the integrated inductor containing iron-based nanocrystalline alloy powder after cooling. The present technical solution improves the problem that the existing iron-based powder is difficult to balance low high-frequency loss and corrosion resistance by the cooperation of uniform precipitation of alpha-Fe nanocrystals, phosphate passivation surface treatment and modification of a silane coupling agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of electronic materials, and more specifically, to an integrally formed inductor containing iron-based nanocrystalline alloy powder and its preparation method. Background Technology

[0002] As a new generation of power inductors, molded inductors have become core components in consumer electronics, automotive electronics, 5G communications, artificial intelligence servers, and aerospace due to their advantages such as low loss, high current, excellent magnetic shielding, and compatibility with surface mount technology (SMT).

[0003] Currently, the soft magnetic powder used in integrally molded inductors mainly uses pure iron powder or iron alloy powder. While pure iron powder has high saturation magnetic induction and good DC bias performance, its intrinsic resistivity is low, making it prone to large eddy current losses under high-frequency magnetic fields. At the same time, the surface of pure iron powder is prone to oxidation and corrosion, which leads to damage to the powder insulation layer, deterioration of the magnetic core performance, and insufficient stability in long-term use. Iron alloy powder can improve the corrosion resistance and resistivity of the powder by introducing elements such as Cr, Si, and Al, but at higher frequencies, hysteresis loss, eddy current loss, and residual loss are still significant, leading to increased heat generation of the magnetic core and increased temperature rise of the inductor, which is not conducive to use in high-frequency, high-current scenarios.

[0004] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of this disclosure. Summary of the Invention

[0005] The purpose of this disclosure is to provide an integrally molded inductor containing iron-based nanocrystalline alloy powder and its preparation method, thereby solving the problem that existing integrally molded inductors using iron-based powders are difficult to balance low high-frequency loss and corrosion resistance.

[0006] Other features and advantages of this disclosure will become apparent from the following detailed description, or may be learned in part from practice of this disclosure.

[0007] According to one aspect of this disclosure, a method for preparing an integrally molded inductor containing iron-based nanocrystalline alloy powder is provided, the steps of which include: S1. The iron-based alloy is melted and wound to form a wound magnetic core. The wound magnetic core is then vacuum annealed to promote the uniform precipitation of α-Fe nanocrystals, resulting in a crystallized strip. S2. The crystallized strip is crushed and ball-milled for a preset time to obtain ball-milled powder. The ball-milled powder is then added to a phosphate passivation solution for surface treatment to obtain phosphated magnetic powder. S3. Phosphated magnetic powder and modified components are mixed and granulated, hot-pressed to form an inductor green blank, then cured and cooled to obtain an integrally formed inductor containing iron-based nanocrystalline alloy powder, wherein the modified components include silane coupling agent.

[0008] According to one aspect of this disclosure, a monolithically molded inductor containing iron-based nanocrystalline alloy powder is provided, which is manufactured by the method for preparing a monolithically molded inductor containing iron-based nanocrystalline alloy powder as described above, wherein... α-Fe nanocrystals are used to reduce the magnetic loss of integrally molded inductors. Phosphate passivation solution is used to form an insulating layer on the surface of ball-milled powder. Silane coupling agents are used to enhance the flowability of phosphating magnetic powder.

[0009] As can be seen from the above technical solutions, the exemplary embodiments disclosed herein possess at least the following advantages and positive effects: In some embodiments of this disclosure, the technical solutions provided, on the one hand, solve the problem that when pure iron powder or conventional iron alloy powder is directly used in existing integrally molded inductors, the soft magnetic structure inside the magnetic powder is not uniform and the permeability and high-frequency loss are difficult to balance. This solves the problem that when pure iron powder or conventional iron alloy powder is directly used in existing integrally molded inductors, the permeability and high-frequency loss are difficult to balance. This results in the formation of a uniformly precipitated α-Fe nanocrystal structure inside the crystallized strip, thereby achieving the basic technical effect of improving the stability of the soft magnetic properties of iron-based magnetic powder, improving the permeability and reducing subsequent high-frequency loss.

[0010] On the other hand, by crushing and ball milling crystallized strip into ball mill powder, and then adding the ball mill powder to a phosphate passivation solution for surface treatment to obtain phosphated magnetic powder, the technical means of obtaining phosphated magnetic powder further overcomes the problems of easy oxidation and poor corrosion resistance of existing pure iron powder or iron-based alloy powder, as well as the problem that direct contact between particles can easily lead to increased high-frequency loss. This allows the magnetic powder surface to obtain a stable surface state after phosphate passivation treatment, thereby achieving the technical effects of improving the corrosion resistance stability of magnetic powder, reducing unfavorable contact between particles, and improving high-frequency loss.

[0011] Meanwhile, by mixing and granulating phosphating magnetic powder with a modifying component including a silane coupling agent, and then hot-pressing and curing it to form an integral inductor, the technical means of forming an integral inductor further overcomes the problems of insufficient dispersion uniformity of nanocrystalline alloy powder during the forming process, poor bonding stability with the forming system, and insufficient structural reliability after forming. This enables phosphating magnetic powder to participate more stably in granulation and hot-pressing curing under the action of the modifying component, thereby achieving the technical effects of improving the forming stability of the inductor green blank, enhancing the integrity of the integral structure after curing, and reducing performance fluctuations.

[0012] In summary, this technical solution, through the continuous combination of uniform precipitation of α-Fe nanocrystals, crushing and ball milling to produce powder, phosphate passivation surface treatment, and silane coupling agent modification granulation hot pressing curing molding, enables the iron-based nanocrystalline alloy powder to possess both a relatively stable soft magnetic property base and good surface stability and molding adaptability. This comprehensively improves the problem that existing integrally molded iron-based powders for inductors are unable to simultaneously achieve low high-frequency loss and corrosion resistance.

[0013] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Attached Figure Description

[0014] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this disclosure and, together with the description, serve to explain the principles of this disclosure. It is obvious that the drawings described below are merely some embodiments of this disclosure, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort. In the drawings: Figure 1 This is a schematic flowchart illustrating a method for preparing an integrally molded inductor from iron-based nanocrystalline alloy powder in one embodiment. Figure 2 This is a physical image of an integrally molded inductor made of iron-based nanocrystalline alloy powder, as described in one embodiment. Figure 3 SEM images of phosphated magnetic powders obtained after treatment with different phosphate passivation systems in the examples and comparative examples; Figure 4 The images show the physical specimens of the iron-based amorphous ribbon and the wound magnetic core obtained in Example 1. Figure 5 These are physical images of the assemblies to be pressed used in various embodiments and comparative experiments. Detailed Implementation

[0015] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more thorough and complete, and will fully convey the concept of the exemplary embodiments to those skilled in the art.

[0016] Furthermore, the described features or characteristics may be combined in any suitable manner in one or more embodiments. Numerous specific details are provided in the following description to give a thorough understanding of embodiments of this disclosure. However, those skilled in the art will recognize that the technical solutions of this disclosure may be practiced without one or more of the specific details, or other methods, steps, etc. may be employed. In other instances, well-known methods, implementations, or operations are not shown or described in detail to avoid obscuring various aspects of this disclosure.

[0017] The flowcharts shown in the accompanying drawings are merely illustrative and do not necessarily include all content and operations / steps, nor do they necessarily have to be performed in the described order. For example, some operations / steps can be broken down, while others can be combined or partially combined; therefore, the actual execution order may change depending on the specific circumstances.

[0018] like Figure 1 As shown, this invention proposes a method for preparing an integrally molded inductor containing iron-based nanocrystalline alloy powder, the steps of which include: S1. The iron-based alloy is melted and wound to form a wound magnetic core. The wound magnetic core is then vacuum annealed to promote the uniform precipitation of α-Fe nanocrystals, resulting in a crystallized strip. The elemental composition of the iron-based alloy includes Fe, Si, B, Cu, Nb, Mo, and Ni, where Si accounts for 13.5–15.5 at.%, B for 7.0–12.0 at.%, Cu for 0.5–1.5 at.%, Nb for 1.0–3.0 at.%, Mo for 0–2.0 at.%, Ni for 0–20.0 at.%, with Fe as the balance, and contains unavoidable impurities.

[0019] In one embodiment, the elemental composition of the iron-based alloy includes Fe, Si, B, Cu, Nb, Mo, Ni, Zr, and P, wherein Si accounts for 13.0–15.5 at.%, B accounts for 7.0–12.0 at.%, Cu accounts for 0.5–1.5 at.%, Nb accounts for 1.0–3.0 at.%, Mo accounts for 0.2–2.0 at.%, Ni accounts for 3.05–12.0 at.%, Zr accounts for 0.05–0.8 at.%, P accounts for 0.2–1.2 at.%, and Fe is the balance, and it contains unavoidable impurities.

[0020] Step S1 includes: S1.1. Iron-based alloys are added to a medium-frequency induction melting furnace for melting. Before melting, the furnace cavity is evacuated to 5×10⁻⁶. -2 Below Pa, high-purity argon gas is then introduced to 0.02–0.08 MPa, and the vacuuming and argon purging process is repeated 2–3 times. The melting temperature is controlled at 1450–1580℃. After the alloy is completely melted, it is held at this temperature for 3–8 minutes to obtain an iron-based master alloy ingot. S1.2. The iron-based master alloy ingot is added to a gravity melt rapid quenching equipment for strip forming. Before strip forming, the equipment cavity is evacuated to 5×10⁻⁶. -2 Below Pa, high-purity argon gas is introduced to remelt the iron-based master alloy ingot. After cooling, an iron-based amorphous ribbon with a width of 25±0.3 mm and a thickness of 29±1 μm is formed. This ribbon is then wound in the same direction using an automatic winding machine to form a wound magnetic core. The inner diameter of the wound magnetic core is 32 mm and the outer diameter is 50 mm. S1.3. Place the wound magnetic core in a vacuum annealing furnace for annealing treatment, and evacuate the furnace cavity to a vacuum level of 1×10⁻⁶. -1 Below Pa, first heat to 280-450℃ at a heating rate of 2-5℃ / min, hold for 40-80min, then heat to 450-550℃ at a heating rate of 1-3℃ / min, hold for 60-100min, then heat to 550-650℃ at a heating rate of 1-3℃ / min, hold for 90-150min to obtain crystallized strip.

[0021] In one embodiment, step S1.2 further includes: Before winding, the amorphous state of the iron-based amorphous ribbon is detected. The phase structure of the iron-based amorphous ribbon is detected by X-ray diffraction. When the iron-based amorphous ribbon mainly shows amorphous diffuse peaks and no obvious α-Fe crystallization peaks, it is judged to be a qualified ribbon and the qualified ribbon is wound.

[0022] In one embodiment, step S1.3 further includes: During the annealing process, an external magnetic field is applied to the wound magnetic core, and the external magnetic field is applied along the circumferential magnetic path direction of the wound magnetic core. The circumferential magnetic path direction corresponds to the length direction of the iron-based amorphous ribbon after winding. The magnetic field strength is controlled to be 0.05~0.3T.

[0023] In terms of composition, iron is the main magnetic element, providing high magnetic response and saturation magnetic induction. Silicon and boron enhance the alloy's amorphous forming ability, making it easier for the melt to form uniform amorphous ribbons after rapid quenching. Copper readily forms fine enrichment regions during subsequent annealing, serving as nucleation sites for α-iron nanocrystals and resulting in more uniform nanocrystal precipitation. Niobium and molybdenum diffuse slowly and tend to distribute near grain boundaries and residual amorphous phases, limiting excessive growth of α-iron nanocrystals. Nickel is used to adjust soft magnetic properties and alloy processing stability. This combination of elements helps reduce the increased magnetic loss caused by coarse grains and uneven microstructure.

[0024] In embodiments incorporating zirconium and phosphorus, zirconium and phosphorus are further used to enhance grain boundary stabilization. Zirconium atoms diffuse slowly, strengthening the pinning effect at grain boundaries or grain boundary junctions, while phosphorus not only helps improve amorphous formation ability but also participates in the stabilization of grain boundaries and residual amorphous phases.

[0025] During the smelting stage, vacuuming, filling with high-purity argon, and repeated replacement can reduce the entry of impurities such as oxygen and nitrogen into the melt, preventing the oxidation and consumption of active elements. Controlling the smelting temperature at 1450–1580℃ and holding it at that temperature for 3–8 minutes after the alloy is completely melted ensures that iron, silicon, boron, copper, niobium, molybdenum, nickel, and optionally zirconium and phosphorus, are fully and uniformly distributed in the melt, reducing localized segregation.

[0026] In the rapid quenching stage, the iron-based master alloy ingot is remelted and then rapidly quenched by gravity melt to form an iron-based amorphous ribbon. Rapid cooling can be used to suppress the premature formation of coarse crystals, allowing elements such as copper, niobium, and molybdenum to be temporarily dissolved in the amorphous matrix.

[0027] During the winding stage, winding the iron-based amorphous strip into a wound magnetic core with an inner diameter of 32mm and an outer diameter of 50mm in the same direction ensures that the strip maintains uniform specifications and a stable heating state during annealing. Compared to direct annealing of scattered strips, the wound magnetic core has a more regular internal and external structure, making it easier to control the consistency of annealing and also facilitating the application of an external magnetic field along the circumferential magnetic circuit direction of the wound magnetic core in optional solutions.

[0028] In the vacuum segmented annealing stage, the initial holding temperature at 280–450℃ for 40–80 min releases some of the residual stress generated during rapid quenching and winding, and promotes the initial enrichment of copper atoms. The subsequent holding temperature at 450–550℃ for 60–100 min promotes the uniform nucleation of α-iron nanocrystals. Finally, the holding temperature at 550–650℃ for 90–150 min allows the α-iron nanocrystals to further grow to a suitable size, forming a composite structure where α-iron nanocrystals and residual amorphous phases coexist. This composite structure provides good soft magnetic properties and also buffers mechanical stress during subsequent ball milling, reducing the degradation of powder magnetic properties.

[0029] In an optional magnetic field annealing embodiment, an external magnetic field is applied along the circumferential magnetic path direction of the wound magnetic core, which corresponds precisely to the length direction of the wound iron-based amorphous ribbon. This allows the α-iron nanocrystals to be induced by the magnetic field during crystallization, reducing the influence of random magnetic anisotropy and resulting in a crystallized ribbon with lower magnetization resistance and a more stable soft magnetic response.

[0030] S2. The crystallized strip is crushed and ball-milled for a preset time to obtain ball-milled powder. The ball-milled powder is then added to a phosphate passivation solution for surface treatment to obtain phosphated magnetic powder.

[0031] Step S2 includes: S2.1 The crystallized strip is crushed into short segments with a length of 2-10 mm using a roller crusher. During the crushing process, the crusher speed is controlled at 100-500 r / min to obtain crystallized strip short segments. These crystallized strip short segments are then added to a ball mill for the first stage of ball milling. The first stage of ball milling uses grinding balls with a diameter of 15-20 mm, a ball-to-material mass ratio of 5:1-12:1, a ball mill speed controlled at 350-550 r / min, and a ball milling time of 2-10 h. The temperature during the ball milling process is controlled at 20-50℃ to obtain primary crushed powder. S2.2. The primary crushed powder is further subjected to a second stage of ball milling with the addition of process control media. The second stage ball milling uses grinding balls with a diameter of 5–10 mm. The amount of process control media added is 0.2–1.5 wt% of the primary crushed powder mass. The ball milling speed is controlled at 650–780 r / min. Ball milling continues until the cumulative ball milling time reaches 10–25 hours, yielding shaped crushed powder. S2.3. The shaped and crushed powder is then subjected to a third stage of ball milling. The ball milling speed is controlled at 750 rpm, and three diameter grinding balls of 20 mm, 10 mm, and 5 mm are used in combination. Ball milling continues until the cumulative ball milling time reaches 35-50 hours to obtain ball-milled powder. S2.4. Add the ball-milled powder to the phosphate passivation solution for surface treatment. The treatment temperature is controlled at 25-60℃, the stirring speed is controlled at 200-800 r / min, and the treatment time is controlled at 20-90 min to obtain wet phosphate magnetic powder. The wet phosphate magnetic powder is subjected to solid-liquid separation and rinsing with volatile solvent. After rinsing, it is vacuum dried at 60-90℃ for 1-3 h, and then kept at 100-140℃ in an inert atmosphere for 0.5-2 h to obtain phosphate magnetic powder.

[0032] The phosphate passivation solution includes at least one of phosphate-acetone passivation solution, phosphate-ethanol passivation solution, phosphate-isopropanol passivation solution, ammonium dihydrogen phosphate passivation solution, and sodium dihydrogen phosphate passivation solution; the volatile solvent includes at least one of acetone, anhydrous ethanol, isopropanol, and ethyl acetate; and the process control medium includes at least one of anhydrous acetone, anhydrous ethanol, and isopropanol.

[0033] In one embodiment, in step S2.3, intermittent sampling and detection are performed during the third stage ball milling process, with sampling every 4 to 6 hours. The average grain size of α-Fe nanocrystals is calculated using X-ray diffraction. When the average grain size of α-Fe nanocrystals is maintained at 14 to 18 nm, ball milling is stopped to obtain ball-milled powder.

[0034] In one embodiment, between step S2.3 and step S2.4, the following step is further included: The ball-milled powder was placed in an inert atmosphere and heated to 180–260°C at a rate of 1–3°C / min, held at that temperature for 20–80 min, and then cooled to room temperature before being classified. The grading process includes: placing the ball-milled powder in a vibrating sieve, applying an alternating magnetic field of 0.01–0.08 T in the sieving area, and separating it into strong magnetic response powder, medium magnetic response powder, and weak magnetic response tail powder. The particle size of the strong magnetic response powder is 12–35 μm, D50 is 18–24 μm, and D90 is not greater than 38 μm; the particle size of the medium magnetic response powder is 5–18 μm, D50 is 8–12 μm, and D90 is not greater than 22 μm; and the particle size of the weak magnetic response tail powder is 0.3–8 μm, and D50 is 1–4 μm. The powder is then compounded according to the following proportions: strong magnetic response powder 60–75 wt%, medium magnetic response powder 20–35 wt%, and weak magnetic response tail powder 0–8 wt%. In one embodiment, the grading process includes: placing the ball-milled powder in an air classifier, using nitrogen or dry air as the dispersing gas, controlling the dispersing gas pressure to be 0.05–0.3 MPa, and controlling the classifier wheel speed to be 1000–4000 r / min, separating it into coarse powder, medium powder, and fine powder. The coarse powder has a particle size of 20–35 μm and a D50 of 24–30 μm, the medium powder has a particle size of 8–20 μm and a D50 of 12–16 μm, and the fine powder has a particle size of 0.5–8 μm and a D50 of 2–5 μm, and is compounded according to the ratio of 20–35 wt% coarse powder, 45–65 wt% medium powder, and 10–25 wt% fine powder.

[0035] The first stage of ball milling uses larger grinding balls and lower rotation speed, primarily to break the crystallized strip into primary powder, reducing the damage to α-iron nanocrystals and residual amorphous phases caused by strong impacts. The second stage uses smaller grinding balls and adds process control media such as anhydrous acetone, anhydrous ethanol, or isopropanol to further refine and shape the powder, reducing agglomeration, adhesion, and localized temperature rise. The third stage uses a combination of grinding balls of various diameters to further refine and stabilize the powder, resulting in ball-milled powder with suitable particle size and grain size. During the third stage of ball milling, intermittent sampling and X-ray diffraction calculation of the average grain size of α-iron nanocrystals prevent under- or over-milling. Ball milling is stopped when the average grain size of α-iron nanocrystals is maintained at 14–18 nm, which helps to balance powder refinement and nanocrystalline structure stability. A low-temperature stress treatment at 180–260°C after ball milling releases some residual mechanical stress, reducing the risk of magnetic property fluctuations during subsequent pressing and curing.

[0036] Classification is used to optimize powder composition. Magnetic field classification can separate powders with strong magnetic response, medium magnetic response, and weak magnetic response tail powder according to the differences in magnetic response, reducing the influence of weak magnetic powder, fine oxidized powder, and overly fine powder on magnetic properties. Airflow classification can obtain coarse, medium, and fine powders according to particle size differences, and improve the powder bulk density and subsequent hot pressing compactness through reasonable blending.

[0037] During the phosphating stage, phosphate ions in the phosphate passivation solution react with iron, iron oxides, niobium, molybdenum, zirconium, and their oxides or hydroxyl sites on the surface of the ball-milled powder to form an insulating layer of iron phosphate, niobium phosphate, molybdenum phosphate, zirconium phosphate, or composite metal phosphate. This insulating layer isolates adjacent magnetic powder particles, reducing the conductive path between particles and thus lowering high-frequency eddy current losses. Subsequent rinsing with volatile solvents such as acetone, anhydrous ethanol, isopropanol, or ethyl acetate removes free acid and residual passivation solution, reducing the risk of corrosion during subsequent resin coating and hot pressing.

[0038] S3. Phosphated magnetic powder and modified components are mixed and granulated, hot-pressed to form an inductor green blank, then cured and cooled to obtain an integrally formed inductor containing iron-based nanocrystalline alloy powder, wherein the modified components include silane coupling agent.

[0039] Step S3 includes: S3.1 Preheat the phosphating magnetic powder at a temperature of 50–80°C, with a stirring speed of 100–400 r / min and a processing time of 10–30 min to obtain preheated phosphating magnetic powder. Add a silane coupling agent to the preheated phosphating magnetic powder for interface modification. The amount of silane coupling agent added is 0.2–1.5 wt% of the mass of the phosphating magnetic powder. Control the modification temperature at 50–85°C, with a stirring speed of 200–600 r / min and a modification time of 20–60 min. Then pre-dry at 70–100°C for 20–60 min to obtain silane-modified magnetic powder. S3.2. Add the silane-modified magnetic powder to a wet granulator for granulation. Control the granulation temperature at 50–90℃ and the granulation time at 20–80 min. After granulation, sieve the powder to obtain composite magnetic powder particles with a particle size of 60–180 μm. S3.3. Fix the pre-made coil at the center of the cavity, then fill the cavity with composite magnetic powder particles in stages. The cavity size is 7.1mm × 6.5mm × 3.0mm, resulting in the assembly to be pressed. Perform hot pressing on the assembly, controlling the molding temperature at 140–180℃, the molding pressure at 500–850MPa, the pressure increase rate at 20–80MPa / s, and the holding time at 120–240s, to obtain the inductor blank. S3.4. Perform staged curing treatment on the inductor preform. First, keep it at 100-130℃ for 20-60 minutes, then raise the temperature to 180-220℃ and keep it at 40-90 minutes, then raise the temperature to 230-330℃ and keep it at 10-40 minutes. After the temperature is maintained, cool it to below 120℃ at a cooling rate of 0.5-3℃ / min, and then let it cool naturally to room temperature to obtain the cured inductor preform.

[0040] The modified components also include silicon-based heat-resistant components, heat-resistant resin binders, curing agents, and lubricants. Between steps S3.1 and S3.2, the following is also included: A silicon-based heat-resistant component was added to silane-modified magnetic powder to construct a heat-resistant interface. The amount of silicon-based heat-resistant component added was 0.3–2.0 wt% of the phosphating magnetic powder. Ethanol and deionized water were added as hydrolysis dispersion media. The hydrolysis temperature was controlled at 40–70 °C, and the reaction time was controlled at 30–90 min. Then add heat-resistant resin binder, curing agent and lubricant and mix. The amount of heat-resistant resin binder added is 1.0 to 4.0 wt% of the mass of phosphated magnetic powder, the amount of curing agent added is 2 to 15 wt% of the mass of heat-resistant resin binder, and the amount of lubricant added is 0.1 to 0.8 wt% of the mass of phosphated magnetic powder. The mixing temperature is controlled at 60 to 90°C and the mixing time is controlled at 20 to 60 min.

[0041] The silane coupling agent includes at least one of aminosilane coupling agents, epoxysilane coupling agents, vinylsilane coupling agents, methacryloxysilane coupling agents, and mercaptosilane coupling agents; the silicon-based heat-resistant component includes at least one of silica sol, tetraethyl orthosilicate, and methyltriethoxysilane; the heat-resistant resin binder includes at least one of modified epoxy resin, organosilicon resin, phenolic resin, and polyimide precursor; the curing agent includes at least one of imidazole curing agents, acid anhydride curing agents, and phenolic curing agents; and the lubricant includes at least one of zinc stearate, calcium stearate, polyethylene wax, and paraffin wax.

[0042] During the silane coupling agent modification stage, the surface of the phosphated magnetic powder contains a phosphate layer, metal oxide, or hydroxyl sites. After hydrolysis, the silane coupling agent can bind to these inorganic sites, while its organic end groups can be compatible with or react with the subsequent resin binder, thus forming an interfacial bridging layer between the phosphated magnetic powder and the resin. This treatment can improve the bonding strength between the magnetic powder and the resin, reducing problems such as phosphate layer peeling, resin cracking, or localized insulation failure during hot pressing and curing.

[0043] When further silicon-based heat-resistant components are added, silica sol, tetraethyl orthosilicate, or methyltriethoxysilane can undergo hydrolysis and condensation in the presence of ethanol and water to form a silicon-oxygen network layer on the surface of the magnetic powder. This silicon-oxygen network layer has good heat resistance and can enhance the interfacial strength between the phosphate layer and the resin layer, reducing the decrease in insulation caused by resin shrinkage, softening, or debonding during high-temperature curing and long-term operation.

[0044] Heat-resistant resin binders are used to bond composite magnetic powder particles into a monolithic magnetic core structure. Modified epoxy resin, silicone resin, phenolic resin, or polyimide precursors form a bonding network after curing, fixing the magnetic powder particles and coils together. Curing agents promote resin cross-linking and curing, while lubricants such as zinc stearate, calcium stearate, polyethylene wax, or paraffin wax reduce friction between particles and between particles and the mold, making it easier for the magnetic powder to fill the cavity and reducing the risk of pressing cracks and damage to the coil insulation layer.

[0045] The granulation step transforms fine phosphating magnetic powder into composite magnetic powder particles with a particle size of 60–180 μm, which improves powder flowability, reduces fine powder agglomeration, and allows the magnetic powder to fill the cavity more evenly. Fixing the pre-made coil in the center of the cavity and filling it with composite magnetic powder particles in stages reduces coil offset, allows the magnetic powder to coat the coil more evenly, and improves the consistency of inductor products.

[0046] The hot pressing stage is carried out at 140–180℃ and 500–850 MPa, allowing the composite magnetic powder particles to be gradually compacted while the resin is softened or semi-cured. This method not only improves the density of the magnet but also utilizes the resin layer and lubricant to buffer the hard contact between particles, reducing the risk of magnetic powder particles damaging the coil insulation layer.

[0047] Staged curing allows the resin to gradually level, remove residual volatiles, complete curing, and release some stress. First, holding at 100–130°C helps remove residual solvents and low-molecular-weight substances. Then, holding at 180–220°C ensures full resin curing. Finally, a short-term holding at 230–330°C helps homogenize residual stress generated during hot pressing and curing. Subsequent cooling at 0.5–3°C / min to below 120°C, followed by natural cooling to room temperature, reduces interfacial stress caused by differences in thermal expansion between the magnetic powder, resin, silicon oxide network layer, and coil.

[0048] When the heat-resistant resin binder is an epoxy resin / imidazolium curing system, the curing temperature is controlled at 90–170℃; when the heat-resistant resin binder is an epoxy resin / anhydride curing system, the curing temperature is controlled at 100–190℃; when the heat-resistant resin binder is a phenolic resin system, the curing temperature is controlled at 100–220℃; when the heat-resistant resin binder is an organosilicon resin system, the curing temperature is controlled at 100–240℃; when the heat-resistant resin binder is a polyimide precursor system, a step-imidization treatment is performed in an inert atmosphere, the imidization temperature is controlled at 100–320℃, and after cooling, a cured inductor preform is obtained.

[0049] Please refer to Figure 2 This invention proposes a one-piece molded inductor made of iron-based nanocrystalline alloy powder, which is manufactured by a method for preparing the one-piece molded inductor made of iron-based nanocrystalline alloy powder. α-Fe nanocrystals are used to reduce the magnetic loss of integrally molded inductors. Phosphate passivation solution is used to form an insulating layer on the surface of ball-milled powder. Silane coupling agents are used to enhance the flowability of phosphating magnetic powder.

[0050] Example 1: In this embodiment, the elemental composition of the iron-based alloy, by atomic percentage, is: Fe 67.0 at.%, Si 14.5 at.%, B 9.0 at.%, Cu 1.0 at.%, Nb 2.0 at.%, Mo 0.8 at.%, and Ni 5.7 at.%. The iron-based alloy is added to a medium-frequency induction melting furnace for melting. Before melting, the furnace cavity is evacuated to 5 × 10⁻⁶. -2 Below Pa, high-purity argon gas is introduced to 0.05 MPa, and the vacuuming and argon filling are repeated 3 times. The melting temperature is controlled at 1520℃. After the alloy is completely melted, it is held at the temperature for 5 minutes to obtain the iron-based master alloy ingot.

[0051] The iron-based master alloy ingot is added to a gravity melt rapid quenching equipment for strip forming. Before strip forming, the equipment cavity is evacuated to 5×10⁻⁶. -2 Below Pa, high-purity argon gas is introduced to remelt the iron-based master alloy ingot. After cooling, an iron-based amorphous ribbon with a width of 25.0 mm and a thickness of 29 μm is formed. This ribbon is then wound in the same direction using an automatic winding machine to form a wound magnetic core with an inner diameter of 32 mm and an outer diameter of 50 mm. The wound magnetic core is then placed in a vacuum annealing furnace for annealing treatment. The furnace chamber is evacuated to below 1 × 10^-1 Pa. The temperature is first increased to 380 °C at a heating rate of 3 °C / min and held for 60 min. Then, the temperature is increased to 500 °C at a heating rate of 2 °C / min and held for 80 min. Finally, the temperature is increased to 580 °C at a heating rate of 2 °C / min and held for 120 min to obtain the crystallized ribbon.

[0052] The crystallized strip was crushed into short segments with a length of 2-10 mm using a roller crusher. The crusher speed was controlled at 300 r / min during the crushing process to obtain crystallized strip segments. These segments were then fed into a ball mill for the first stage of ball milling. The first stage used 20 mm diameter grinding balls at a ball-to-material mass ratio of 8:1, with a milling speed controlled at 450 r / min and a milling time of 6 hours. The temperature during milling was controlled at 20-50℃, yielding primary crushed powder. The primary crushed powder was then subjected to a second stage of ball milling, with anhydrous ethanol added as the process control medium. The amount of anhydrous ethanol added was 0.8 wt% of the primary crushed powder mass. The second stage used 8 mm diameter grinding balls at a milling speed controlled at 700 r / min, and milling continued until the cumulative milling time reached 20 hours, yielding shaped crushed powder. The shaped and crushed powder is subjected to a third stage of ball milling. The ball milling speed is controlled at 750 rpm, and the grinding balls are made of three diameters: 20 mm, 10 mm, and 5 mm. The ball milling continues until the cumulative ball milling time reaches 40 hours, and the ball milled powder is obtained.

[0053] The ball-milled powder was added to a phosphoric acid-acetone passivation solution for surface treatment. The volume ratio of phosphoric acid to acetone in the passivation solution was 1:20, and the amount of phosphoric acid was 2.5 wt% of the ball-milled powder. The treatment temperature was controlled at 40℃, the stirring speed was controlled at 500 r / min, and the treatment time was 60 min, resulting in wet phosphating magnetic powder. The wet phosphating magnetic powder was subjected to solid-liquid separation and washed with acetone. After washing, it was vacuum dried at 80℃ for 2 h, and then kept at 120℃ under a nitrogen atmosphere for 1 h to obtain phosphating magnetic powder.

[0054] Phosphated magnetic powder was preheated at 65℃ with a stirring speed of 250 r / min for 20 min to obtain preheated phosphated magnetic powder. An epoxy-based silane coupling agent was added to the preheated phosphated magnetic powder for interfacial modification at 0.8 wt% of the phosphated magnetic powder mass. The modification temperature was controlled at 70℃ with a stirring speed of 400 r / min for 40 min. The powder was then pre-dried at 85℃ for 40 min to obtain silane-modified magnetic powder. The silane-modified magnetic powder was then granulated in a wet granulator at 70℃ for 50 min. After granulation, the powder was sieved to obtain composite magnetic powder particles with a particle size of 60–180 μm.

[0055] The pre-fabricated coil is fixed at the center of the cavity, and then composite magnetic powder particles are filled into the cavity in stages. The cavity used for testing is a ring structure with an outer diameter of 20 mm, an inner diameter of 12 mm, and a height of 5 mm, resulting in the assembly to be pressed. The ring structure has a closed magnetic circuit, low magnetic leakage, and a relatively uniform magnetic field distribution, which allows for relatively accurate testing of the magnetic permeability, loss, DC bias performance, and frequency stability of the magnetic powder material itself. The assembly to be pressed is then hot-pressed into a single piece. The molding temperature is controlled at 160℃, the molding pressure at 700 MPa, the pressure increase rate at 50 MPa / s, and the holding time at 180 s, resulting in the inductor green blank. The inductor blank is subjected to a staged curing process. First, it is heated to 120℃ for 40 minutes, then heated to 200℃ and held for 60 minutes, then heated to 250℃ and held for 20 minutes. After the holding is completed, it is cooled to below 120℃ at a cooling rate of 2℃ / min, and then naturally cooled to room temperature to obtain an integrally formed inductor containing iron-based nanocrystalline alloy powder.

[0056] Example 2: In this embodiment, the elemental composition of the iron-based alloy by atomic percentage is: Fe 66.5 at.%, Si 14.5 at.%, B 9.2 at.%, Cu 1.0 at.%, Nb 2.2 at.%, Mo 0.8 at.%, and Ni 5.8 at.%. The melting, rapid quenching, and winding conditions are basically the same as in Example 1. The difference lies in that, before winding, an X-ray diffractometer is used to detect the phase structure of the iron-based amorphous ribbon. When the iron-based amorphous ribbon mainly exhibits amorphous diffuse peaks and no obvious α-Fe crystallization peaks, it is determined to be a qualified ribbon, and then the qualified ribbon is wound to form a wound magnetic core.

[0057] The vacuum annealing conditions in this embodiment are the same as in Example 1. During ball milling, the first stage ball milling conditions are the same as in Example 1. In the second stage, anhydrous acetone is used as the process control medium, and the amount of anhydrous acetone added is 1.0 wt% of the mass of the primary crushed powder. Ball milling continues until the cumulative ball milling time reaches 18 hours, yielding shaped crushed powder. In the third stage ball milling, samples are taken every 5 hours, and the average grain size of α-Fe nanocrystals is calculated using X-ray diffraction. Ball milling is stopped when the average grain size of α-Fe nanocrystals remains between 14 and 18 nm. The actual cumulative ball milling time is 38 hours, yielding ball-milled powder.

[0058] In this embodiment, the phosphating treatment uses a phosphoric acid-ethanol passivation solution with a phosphoric acid to ethanol volume ratio of 1:20. The amount of phosphoric acid used is 2.2 wt% of the ball mill powder mass. The treatment temperature is 40°C, and the treatment time is 60 min. Anhydrous ethanol is used as the volatile solvent. An aminosilane coupling agent is used, and the amount added is 1.0 wt% of the phosphating magnetic powder mass. The remaining granulation, hot pressing, and staged curing conditions are the same as in Example 1.

[0059] Example 3: In this embodiment, the elemental composition of the iron-based alloy by atomic percentage is: Fe 68.0 at.%, Si 14.0 at.%, B 9.0 at.%, Cu 1.0 at.%, Nb 2.0 at.%, Mo 1.0 at.%, and Ni 5.0 at.%. The melting, strip making, amorphous state detection, and winding conditions are the same as in Example 2. During the annealing process, an external magnetic field is applied to the wound magnetic core, with the field applied along the circumferential magnetic path direction of the core, corresponding to the length direction of the wound iron-based amorphous strip. The magnetic field strength is controlled at 0.15T. The annealing regime is as follows: first, the temperature is increased to 380℃ at 3℃ / min and held for 60min; then, the temperature is increased to 500℃ at 2℃ / min and held for 90min; finally, the temperature is increased to 570℃ at 2℃ / min and held for 120min, resulting in a crystallized strip.

[0060] During the ball milling process, the first stage of ball milling conditions were the same as in Example 1. In the second stage, isopropanol was used as the process control medium, and the amount of isopropanol added was 0.8 wt% of the mass of the primary crushed powder. Ball milling continued until the cumulative ball milling time reached 20 h. In the third stage of ball milling, samples were taken every 5 h. Ball milling was stopped when the average grain size of α-Fe nanocrystals remained at 14–18 nm. The actual cumulative ball milling time was 39 h, and the ball-milled powder was obtained.

[0061] Phosphating was performed using a phosphoric acid-isopropanol passivation solution, with a phosphoric acid to isopropanol volume ratio of 1:20. The amount of phosphoric acid used was 2.5 wt% of the ball mill powder. The treatment temperature was 40°C, and the treatment time was 60 min. Isopropanol was used as the volatile solvent. Methacryloxysilane coupling agent was used, and the amount added was 0.8 wt% of the phosphating magnetic powder. The remaining granulation, hot pressing, and staged curing conditions were the same as in Example 1.

[0062] Example 4: In this embodiment, the elemental composition of the iron-based alloy by atomic percentage is: Fe 67.2 at.%, Si 14.3 at.%, B 9.0 at.%, Cu 1.0 at.%, Nb 2.2 at.%, Mo 1.0 at.%, and Ni 5.3 at.%. The melting, strip making, amorphous state detection, winding, and magnetic field annealing steps are the same as in Example 3, with the magnetic field strength controlled at 0.18T. The annealing regime is as follows: first, heat to 390℃ and hold for 60 min, then heat to 500℃ and hold for 90 min, then heat to 570℃ and hold for 130 min, to obtain a crystallized strip.

[0063] The ball milling process was the same as in Example 3, with the actual cumulative ball milling time in the third stage being 40 hours. After ball milling, the milled powder was placed in a nitrogen atmosphere and heated to 220°C at a heating rate of 2°C / min, held at that temperature for 60 minutes, and then cooled to room temperature before undergoing airflow classification. During airflow classification, nitrogen was used as the dispersing gas, with the dispersing gas pressure controlled at 0.15 MPa and the classifier wheel speed controlled at 2500 r / min, yielding coarse, medium, and fine powders. The coarse powder had a particle size of 20–35 μm and a D50 of 27 μm, the medium powder had a particle size of 8–20 μm and a D50 of 14 μm, and the fine powder had a particle size of 0.5–8 μm and a D50 of 3.5 μm. The powder was then blended in a ratio of 30 wt% coarse powder, 55 wt% medium powder, and 15 wt% fine powder to obtain a blended ball-milled powder.

[0064] In this embodiment, ammonium dihydrogen phosphate passivation solution was used for surface treatment. The amount of ammonium dihydrogen phosphate added was 3.0 wt% of the mass of the compound ball milled powder. The treatment temperature was 45°C, the stirring speed was 500 r / min, and the treatment time was 70 min. Anhydrous ethanol was used as the volatile solvent. Vinylsilane coupling agent was used, and the amount added was 0.9 wt% of the mass of the phosphating magnetic powder. The remaining granulation, hot pressing, and staged curing conditions were the same as in Example 1.

[0065] Example 5: In this embodiment, the elemental composition of the iron-based alloy by atomic percentage is: Fe 63.5 at.%, Si 14.5 at.%, B 9.0 at.%, Cu 1.2 at.%, Nb 2.5 at.%, Mo 1.0 at.%, Ni 7.0 at.%, Zr 0.4 at.%, and P 0.9 at.%. The melting and rapid quenching conditions are the same as in Example 1. Before winding, the phase structure of the iron-based amorphous ribbon was examined using X-ray diffraction to confirm that it mainly exhibited amorphous diffuse peaks and no obvious α-Fe crystallization peaks before winding. During annealing, a 0.20T external magnetic field was applied along the circumferential magnetic path of the winding core. The annealing regime was as follows: first, the temperature was raised to 390℃ and held for 60 min; then, the temperature was raised to 500℃ and held for 90 min; finally, the temperature was raised to 570℃ and held for 130 min, resulting in a crystallized ribbon.

[0066] During the ball milling process, the first stage of ball milling lasted for 6 hours. In the second stage, isopropanol was used as the process control medium, with an addition amount of 1.0 wt% of the primary crushed powder. Ball milling continued until the cumulative ball milling time reached 20 hours. In the third stage, samples were taken every 5 hours, and the average grain size of α-Fe nanocrystals was calculated using X-ray diffraction. Ball milling was stopped when the average grain size of α-Fe nanocrystals stabilized at approximately 15.1 nm. The actual cumulative ball milling time was 42 hours. The milled powder was then placed in a nitrogen atmosphere, heated to 220°C at a rate of 2°C / min, held at that temperature for 60 minutes, cooled to room temperature, and then subjected to airflow classification. The powder was then blended in a ratio of 30 wt% coarse powder, 55 wt% medium powder, and 15 wt% fine powder.

[0067] In this embodiment, sodium dihydrogen phosphate passivation solution was used for surface treatment. The amount of sodium dihydrogen phosphate added was 2.8 wt% of the mass of the compound ball milled powder. The treatment temperature was 45℃, the stirring speed was 500 r / min, and the treatment time was 70 min. The volatile solvent used was a mixed solvent of ethyl acetate and isopropanol, with a mass ratio of ethyl acetate to isopropanol of 1:1, to obtain phosphated magnetic powder.

[0068] In this embodiment, the silane coupling agent is a mixture of epoxy silane coupling agent and amino silane coupling agent in a mass ratio of 7:3, with a total addition amount of 1.2 wt% of the phosphating magnetic powder mass. The silicon-based heat-resistant component is a mixture of tetraethyl orthosilicate and methyltriethoxysilane in a molar ratio of 2:1, with a total addition amount of 1.5 wt% of the phosphating magnetic powder mass. Ethanol is added as a dispersion solvent, and the amount of deionized water added is calculated based on the sum of the number of ethoxy moles in tetraethyl orthosilicate and the number of ethoxy moles in methyltriethoxysilane, ensuring that the number of moles of deionized water is 1 times the total number of moles of alkoxy groups. Subsequently, the pH of the system is adjusted to 4.0–5.0, and hydrolysis and condensation are performed at 60°C for 70 min. Subsequently, modified epoxy resin and silicone resin were added as heat-resistant resin binders in a mass ratio of 7:3, with a total addition amount of 3.0 wt% of the phosphating magnetic powder. An acid anhydride curing agent was added, with an addition amount of 10 wt% of the heat-resistant resin binder. Calcium stearate and polyethylene wax were added as lubricants in a mass ratio of 1:1, with a total addition amount of 0.5 wt% of the phosphating magnetic powder. The mixing temperature was 80℃, and the mixing time was 50 min.

[0069] The above mixture was added to a wet granulator for granulation at a temperature of 75°C for 60 minutes. The granulation was then sieved to obtain composite magnetic powder particles with a particle size of 60–180 μm. Subsequently, a pre-formed coil was fixed at the center of the cavity, and the composite magnetic powder particles were added in stages at a molding temperature of 165°C, a molding pressure of 750 MPa, a pressure increase rate of 50 MPa / s, and a holding time of 200 s to obtain an inductor green blank. The inductor green blank was then sequentially held at 120°C for 40 minutes, 200°C for 70 minutes, and 250°C for 30 minutes, followed by cooling to below 120°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain an integrally formed inductor containing iron-based nanocrystalline alloy powder.

[0070] Comparative Example 1: The only difference between Comparative Example 1 and Example 1 is that the vacuum annealing process in step S1.3 is omitted. Instead, the iron-based amorphous ribbon obtained in step S1.2 is directly crushed and ball-milled, followed by phosphating, silane modification, granulation, hot pressing, and curing. The remaining iron-based alloy composition, melting conditions, rapid quenching conditions, ball milling conditions, amount of phosphate-acetone passivation solution, amount of epoxy silane coupling agent, and hot pressing curing conditions are all the same as in Example 1.

[0071] Comparative Example 2: The only difference between Comparative Example 2 and Example 1 is that the phosphate passivation treatment in step S2.4 is omitted. That is, the ball-milled powder is not treated with phosphate-acetone passivation solution, but is directly introduced into the silane modification, granulation, hot pressing and curing steps after only acetone rinsing and drying. The remaining steps are the same as in Example 1.

[0072] Comparative Example 3: The only difference between Comparative Example 3 and Example 1 is that the step of adding an epoxy silane coupling agent for interface modification in step S3.1 is omitted; that is, the phosphating magnetic powder is only preheated and granulated without the addition of a silane coupling agent. The remaining ball milling, phosphating, hot pressing, and curing conditions are the same as in Example 1.

[0073] Comparative Example 4: The only difference between Comparative Example 4 and Example 1 is that the three-stage ball milling in steps S2.1 to S2.3 is replaced with a single-stage ball milling. Specifically, the short section of the crystallized strip is directly ball-milled at 750 rpm for 40 hours. The grinding balls still use a combination of 20 mm, 10 mm, and 5 mm diameters, but the first stage of low-speed coarse crushing and the second stage of shaping ball milling with process control media are omitted. The remaining phosphating, silane modification, granulation, hot pressing, and curing conditions are the same as in Example 1.

[0074] Experiment 1: The integrally molded inductors prepared in Examples 1-5 and Comparative Examples 1-4 were placed at room temperature for 24 hours to allow the internal resin layer, magnetic powder compact, and coil structure to stabilize. Subsequently, impedance analyzers or inductance testers were used to measure the inductance values ​​at test frequencies of 1 kHz, 500 kHz, and 1 MHz. The effective permeability at the corresponding frequencies was calculated based on the core size, number of coil turns, and inductance value of the integrally molded inductor. Five inductors from each sample group were selected for testing, and the average value after removing obvious outliers was used as the data in Table 1.

[0075] Table 1:

[0076] As shown in Table 1, Examples 1-5 maintained high permeability in the 1kHz to 1MHz range, and the permeability generally increased with the gradual optimization of the process steps. Example 1, using basic crystallization annealing, three-stage ball milling, phosphate passivation, and silane modification, achieved a permeability of 99 at 1MHz, indicating that the basic process can form an iron-based nanocrystalline magnetic powder structure suitable for high-frequency inductors. Example 2, with the addition of amorphous state detection and ball milling endpoint control, increased the permeability to 104 at 1MHz, indicating that the quality of the precursor amorphous material and ball milling endpoint control are beneficial in reducing microstructure fluctuations. Example 3, with the further introduction of circumferential magnetic field annealing, increased the permeability to 109 at 1MHz, indicating that magnetic field annealing can improve the magnetization response of nanocrystalline materials. Example 4, with the addition of low-temperature stress treatment and airflow staged compounding, increased the permeability to 112 at 1MHz, indicating that powder stress release and particle size compounding are beneficial in improving pressing density and high-frequency stability. Example 5 uses a Fe, Si, B, Cu, Nb, Mo, Ni, Zr, P system, and after introducing silicon-based heat-resistant components and a heat-resistant resin system, the magnetic permeability reaches 115 at 1MHz, indicating that grain boundary stabilizing elements and interface modification structures can further improve the overall magnetic properties of the inductor.

[0077] Comparative Example 1, without crystallization annealing, exhibited a permeability of only 61 at 1MHz, indicating that the soft magnetic properties of the magnetic powder were significantly insufficient without the formation of a stable α-Fe nanocrystal / residual amorphous composite structure. Comparative Example 2, without phosphate passivation, still had a permeability of 104 at 1kHz, but this dropped to 86 at 1MHz, indicating that insufficient interparticle insulation leads to accelerated permeability decay at high frequencies. Comparative Example 3, without the addition of a silane coupling agent, had a permeability of 82 at 1MHz, indicating that weak interfacial bonding between the magnetic powder and resin resulted in decreased structural stability of the magnet after pressing and curing. Comparative Example 4, using single-stage ball milling, showed a permeability of 70 at 1MHz, indicating that single-stage high-intensity ball milling easily introduces internal stress and structural defects, which is detrimental to maintaining the soft magnetic response of the iron-based nanocrystalline powder.

[0078] Experiment 2: The DC bias inductance retention rate was tested using a DC bias superposition test device. First, the initial inductance value of each sample without DC bias current was recorded at a test frequency of 1MHz. Then, a 15A DC bias current was applied to the sample, and the inductance value under DC bias was recorded. The inductance retention rate was calculated as "inductance value under 15A DC bias / initial inductance value × 100%". Core loss was tested using a soft magnetic AC loss test system. The samples were placed under AC loss conditions of 1MHz and 50mT, and the copper loss caused by the coil DC resistance was subtracted to obtain the core loss. Thermal stability was tested using a constant temperature aging chamber. Each sample was aged at 125℃ for 500 hours. Before and after aging, the samples were placed at room temperature for 2 hours, and the inductance value at 1MHz was measured. The inductance change rate was calculated as "difference between inductance value after aging and inductance value before aging / inductance value before aging × 100%".

[0079] The experimental data for Experiment 2 are shown in Table 2.

[0080] Table 2:

[0081] As shown in Table 2, the DC bias retention rate of the 15A inductors in Examples 1-5 increased from 76% to 88%, indicating that with gradual process optimization, the inductor's anti-saturation capability under high current conditions was enhanced. Example 1 already possessed basic DC bias stability. Example 2, through amorphous state detection and ball milling endpoint control, made the powder structure more stable, increasing the DC bias retention rate to 79%. Example 3, after introducing magnetic field annealing, increased the DC bias retention rate to 82%, indicating that the improved soft magnetic response induced by the magnetic field helps reduce the attenuation of magnetic properties under high current. Example 4, through low-temperature stress treatment and airflow staged compounding, increased the DC bias retention rate to 85%, indicating that reducing ball milling stress and improving powder packing uniformity are beneficial to improving anti-saturation capability. Example 5 further adopted a Zr-P synergistic composition and a heat-resistant interface modification system, achieving a DC bias retention rate of 88%, indicating that grain boundary stability and interface stability jointly improved the inductor's stability under high current conditions.

[0082] Based on the core loss data, the core loss in Example 1 is 390 mW·cm. -3 Example 5 reduced to 270 mW·cm -3This demonstrates that the proposed solution, through crystallization treatment, staged ball milling, phosphate passivation, silane coupling agent modification, and silicon-based heat-resistant interface construction, can gradually reduce high-frequency losses. Specifically, the phosphate passivation solution forms an insulating layer of iron phosphate, niobium phosphate, molybdenum phosphate, zirconium phosphate, or composite metal phosphate, which increases the interparticle resistance of the magnetic powder and reduces interparticle eddy current losses. The silane coupling agent and silicon-based heat-resistant components improve the interfacial bonding between the phosphate layer and the resin layer, reducing insulation layer damage during hot pressing and curing, thus gradually reducing losses.

[0083] The change rate of inductance after aging at 125℃ for 500 hours showed a rate of 5.8% in Example 1 and a decrease to 2.4% in Example 5, indicating that Example 5 exhibits better thermal stability. This is because Zr and P can synergistically improve the stability of grain boundaries and grain boundary junctions with Nb and Mo, reducing the risk of continued growth of α-Fe nanocrystals at high temperatures. The silicon-oxygen network layer and heat-resistant resin binder can reduce interface debonding or cracking between the phosphating layer, resin layer, and magnetic powder particles, thereby reducing inductance drift after long-term thermal aging.

[0084] Comparative Example 1, without crystallization annealing, had a DC bias retention rate of only 58% and a core loss of 650 mW·cm. -3 The inductance value changed by 10.5% after aging, indicating that the lack of a stable α-Fe nanocrystal structure significantly reduced both the soft magnetic properties and thermal stability of the magnetic powder. Comparative Example 2, without phosphate passivation, showed a core loss increasing to 780 mW·cm⁻¹. -3 This indicates that insufficient interparticle insulation significantly increases high-frequency eddy current losses. Comparative Example 3, without the addition of silane coupling agent, showed a 9.0% change in inductance after aging, indicating that insufficient bonding between the magnetic powder and resin interface leads to decreased interface stability after thermal aging. Comparative Example 4, using single-stage ball milling, achieved a core loss of 610 mW·cm. -3 The inductance value changed by 8.9% after aging, indicating that the internal stress and powder defects introduced by single-stage ball milling will increase high-frequency loss and reduce long-term stability.

[0085] Figure 3SEM images of phosphated magnetic powders obtained after treatment with different phosphate passivation systems are shown. (a) Comparative Example 2: phosphate-free passivated magnetic powder; (b) Example 2: phosphate-ethanol passivated magnetic powder; (c) Example 1: phosphate-acetone passivated magnetic powder; (d) Example 3: phosphate-isopropanol passivated magnetic powder; (e) Example 5: sodium dihydrogen phosphate passivated magnetic powder; and (f) Example 4: ammonium dihydrogen phosphate passivated magnetic powder. As can be seen from the images, in samples with lower phosphate content, the surface of the magnetic powder particles remains relatively rough, with obvious exposed lamellae and sharp edges in some areas. The adhesion between particles is relatively low, but the surface passivation layer may not be continuous. As the phosphate content increases, the particle surface is gradually covered by the phosphate reaction products, the edges are passivated, and the particle surface becomes rougher and denser. This indicates that phosphate reacts with iron, iron oxides, and other metal active sites on the magnetic powder surface to form an iron phosphate or composite metal phosphate passivation layer. As the phosphoric acid content continues to increase, more pronounced agglomeration and bridging occur between some powder particles, the particle boundaries become less distinct, and the local surface coating is thicker. This indicates that excessive phosphoric acid leads to an overly strong phosphating reaction, generating a thicker non-magnetic phosphate layer, which may cause fine particles to stick together, affecting powder flowability and the uniformity of subsequent pressing and filling.

[0086] Figure 4 The images show the physical images of the iron-based amorphous ribbon and the wound magnetic core obtained in Example 1. "Freesurface" refers to the free surface of the iron-based amorphous ribbon, which is the side that does not directly contact the water-cooled copper roller during the rapid quenching of the melt. "Sticksurface" refers to the roller-attached surface of the iron-based amorphous ribbon, which can also be understood as the side that contacts the water-cooled copper roller. In OD-F, OD represents the outer diameter position, and F represents the free surface; therefore, OD-F is the free surface position on the outer diameter side of the wound magnetic core. In ID-F, ID represents the inner diameter position, and F represents the free surface; therefore, ID-F is the free surface position on the inner diameter side of the wound magnetic core. In MD-F, MD represents the middle diameter position, and F represents the free surface; therefore, MD-F is the free surface position in the middle diameter region of the wound magnetic core.

[0087] Figure 5 It is the assembly to be pressed used in various embodiments and comparative experiments, with an outer diameter of 20 mm, an inner diameter of 12 mm, and a height of 5 mm.

[0088] Other embodiments of this disclosure will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of this disclosure that follow the general principles of this disclosure and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of this disclosure are indicated by the following claims.

[0089] It should be understood that this disclosure is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of this disclosure is limited only by the appended claims.

Claims

1. A method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder, characterized in that the steps include... include: S1. The iron-based alloy is melted and wound to form a wound magnetic core. The wound magnetic core is then vacuum annealed to promote the uniform precipitation of α-Fe nanocrystals, resulting in a crystallized strip. S2. The crystallized strip is crushed and ball-milled for a preset time to obtain ball mill powder. The ball mill powder is then added to a phosphate passivation solution for surface treatment to obtain phosphate magnetic powder. Step S2 includes: S2.1 The crystallized strip is crushed into short segments with a length of 2-10 mm using a roller crusher. During the crushing process, the crusher speed is controlled at 100-500 r / min to obtain crystallized strip short segments. These crystallized strip short segments are then added to a ball mill for the first stage of ball milling. The first stage of ball milling uses grinding balls with a diameter of 15-20 mm, a ball-to-material mass ratio of 5:1-12:1, a ball mill speed controlled at 350-550 r / min, and a ball milling time of 2-10 h. The temperature during the ball milling process is controlled at 20-50℃ to obtain primary crushed powder. S2.

2. The primary crushed powder is further subjected to a second stage of ball milling with the addition of process control media. The second stage ball milling uses grinding balls with a diameter of 5–10 mm. The amount of process control media added is 0.2–1.5 wt% of the primary crushed powder mass. The ball milling speed is controlled at 650–780 r / min. Ball milling continues until the cumulative ball milling time reaches 10–25 hours, yielding shaped crushed powder. S2.

3. The shaped and crushed powder is then subjected to a third stage of ball milling. The ball milling speed is controlled at 750 rpm, and three diameter grinding balls of 20 mm, 10 mm, and 5 mm are used in combination. Ball milling continues until the cumulative ball milling time reaches 35-50 hours to obtain ball-milled powder. S2.

4. Add the ball-milled powder to the phosphate passivation solution for surface treatment. The treatment temperature is controlled at 25-60℃, the stirring speed is controlled at 200-800 r / min, and the treatment time is controlled at 20-90 min to obtain wet phosphating magnetic powder. The wet phosphating magnetic powder is subjected to solid-liquid separation and rinsing with volatile solvent. After rinsing, it is vacuum dried at 60-90℃ for 1-3 h, and then kept at 100-140℃ in an inert atmosphere for 0.5-2 h to obtain phosphating magnetic powder. S3. Phosphated magnetic powder and modified components are mixed and granulated, hot-pressed to form an inductor green blank, then cured and cooled to obtain an integrally formed inductor containing iron-based nanocrystalline alloy powder, wherein the modified components include silane coupling agent.

2. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 1, characterized in that, Step S1 includes: S1.

1. Iron-based alloys are added to a medium-frequency induction melting furnace for melting. Before melting, the furnace cavity is evacuated to 5×10⁻⁶. -2 Below Pa, high-purity argon gas is then introduced to 0.02–0.08 MPa, and the vacuuming and argon purging process is repeated 2–3 times. The melting temperature is controlled at 1450–1580℃. After the alloy is completely melted, it is held at this temperature for 3–8 minutes to obtain an iron-based master alloy ingot. S1.

2. The iron-based master alloy ingot is added to a gravity melt rapid quenching equipment for strip forming. Before strip forming, the equipment cavity is evacuated to 5×10⁻⁶. -2 Below Pa, high-purity argon gas is introduced to remelt the iron-based master alloy ingot. After cooling, an iron-based amorphous ribbon with a width of 25±0.3 mm and a thickness of 29±1 μm is formed. This ribbon is then wound in the same direction using an automatic winding machine to form a wound magnetic core. The inner diameter of the wound magnetic core is 32 mm and the outer diameter is 50 mm. S1.

3. Place the wound magnetic core in a vacuum annealing furnace for annealing treatment, and evacuate the furnace cavity to a vacuum level of 1×10⁻⁶. -1 Below Pa, first heat to 280-450℃ at a heating rate of 2-5℃ / min, hold for 40-80min, then heat to 450-550℃ at a heating rate of 1-3℃ / min, hold for 60-100min, then heat to 550-650℃ at a heating rate of 1-3℃ / min, hold for 90-150min to obtain crystallized strip.

3. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 2, characterized in that, Step S1.2 also includes: Before winding, the amorphous state of the iron-based amorphous ribbon is detected. The phase structure of the iron-based amorphous ribbon is detected by X-ray diffraction. When the iron-based amorphous ribbon mainly shows amorphous diffuse peaks and no obvious α-Fe crystallization peaks, it is judged to be a qualified ribbon and the qualified ribbon is wound.

4. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 2 or 3, characterized in that, Step S1.3 also includes: During the annealing process, an external magnetic field is applied to the wound magnetic core, and the external magnetic field is applied along the circumferential magnetic path direction of the wound magnetic core. The circumferential magnetic path direction corresponds to the length direction of the iron-based amorphous ribbon after winding. The magnetic field strength is controlled to be 0.05~0.3T.

5. A method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 1 or 2, characterized in that, The elemental composition of iron-based alloys includes Fe, Si, B, Cu, Nb, Mo, and Ni, where Si accounts for 13.5–15.5 at.%, B for 7.0–12.0 at.%, Cu for 0.5–1.5 at.%, Nb for 1.0–3.0 at.%, Mo for 0–2.0 at.%, Ni for 0–20.0 at.%, and Fe is the balance. They also contain unavoidable impurities, or... The elemental composition of iron-based alloys includes Fe, Si, B, Cu, Nb, Mo, Ni, Zr, and P, of which Si accounts for 13.0–15.5 at.%, B for 7.0–12.0 at.%, Cu for 0.5–1.5 at.%, Nb for 1.0–3.0 at.%, Mo for 0.2–2.0 at.%, Ni for 3.05–12.0 at.%, Zr for 0.05–0.8 at.%, P for 0.2–1.2 at.%, with Fe as the balance, and contains unavoidable impurities.

6. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 1, characterized in that, In step S2.3, intermittent sampling and testing are performed during the third stage of ball milling, with samples taken every 4 to 6 hours. The average grain size of α-Fe nanocrystals is calculated using X-ray diffraction. When the average grain size of α-Fe nanocrystals is maintained at 14 to 18 nm, ball milling is stopped to obtain ball-milled powder.

7. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 1, characterized in that, Between steps S2.3 and S2.4, the following also applies: The ball-milled powder was placed in an inert atmosphere and heated to 180–260°C at a rate of 1–3°C / min, held at that temperature for 20–80 min, and then cooled to room temperature before being classified. The grading process includes: The ball-milled powder is placed in a vibrating sieve, and an alternating magnetic field of 0.01–0.08 T is applied in the sieving area. It is then separated into strong magnetic response powder, medium magnetic response powder, and weak magnetic response tail powder. The particle size of the strong magnetic response powder is 12–35 μm, D50 is 18–24 μm, and D90 is not greater than 38 μm. The particle size of the medium magnetic response powder is 5–18 μm, D50 is 8–12 μm, and D90 is not greater than 22 μm. The particle size of the weak magnetic response tail powder is 0.3–8 μm, and D50 is 1–4 μm. The powder is compounded according to the following proportions: strong magnetic response powder 60–75 wt%, medium magnetic response powder 20–35 wt%, and weak magnetic response tail powder 0–8 wt%. The ball-milled powder is placed in an air classifier, using nitrogen or dry air as the dispersing gas. The dispersing gas pressure is controlled at 0.05–0.3 MPa, and the classifier wheel speed is controlled at 1000–4000 r / min. The powder is divided into coarse, medium, and fine powders. The coarse powder has a particle size of 20–35 μm and a D50 of 24–30 μm, the medium powder has a particle size of 8–20 μm and a D50 of 12–16 μm, and the fine powder has a particle size of 0.5–8 μm and a D50 of 2–5 μm. The powders are compounded in a ratio of 20–35 wt% coarse powder, 45–65 wt% medium powder, and 10–25 wt% fine powder.

8. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 1, characterized in that, In step S2, the phosphate passivation solution includes at least one of phosphate-acetone passivation solution, phosphate-ethanol passivation solution, phosphate-isopropanol passivation solution, ammonium dihydrogen phosphate passivation solution, and sodium dihydrogen phosphate passivation solution; the volatile solvent includes at least one of acetone, anhydrous ethanol, isopropanol, and ethyl acetate; and the process control medium includes at least one of anhydrous acetone, anhydrous ethanol, and isopropanol.

9. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 1, characterized in that, Step S3 includes: S3.1 Preheat the phosphating magnetic powder at a temperature of 50–80°C, with a stirring speed of 100–400 r / min and a processing time of 10–30 min to obtain preheated phosphating magnetic powder. Add a silane coupling agent to the preheated phosphating magnetic powder for interface modification. The amount of silane coupling agent added is 0.2–1.5 wt% of the mass of the phosphating magnetic powder. Control the modification temperature at 50–85°C, with a stirring speed of 200–600 r / min and a modification time of 20–60 min. Then pre-dry at 70–100°C for 20–60 min to obtain silane-modified magnetic powder. S3.

2. Add the silane-modified magnetic powder to a wet granulator for granulation. Control the granulation temperature at 50–90℃ and the granulation time at 20–80 min. After granulation, sieve the powder to obtain composite magnetic powder particles with a particle size of 60–180 μm. S3.

3. Fix the pre-made coil at the center of the cavity, then fill the cavity with composite magnetic powder particles in stages. The cavity size is 7.1mm × 6.5mm × 3.0mm, resulting in the assembly to be pressed. Perform hot pressing on the assembly, controlling the molding temperature at 140–180℃, the molding pressure at 500–850MPa, the pressure increase rate at 20–80MPa / s, and the holding time at 120–240s, to obtain the inductor blank. S3.

4. Perform staged curing treatment on the inductor preform. First, keep it at 100-130℃ for 20-60 minutes, then raise the temperature to 180-220℃ and keep it at 40-90 minutes, then raise the temperature to 230-330℃ and keep it at 10-40 minutes. After the temperature is maintained, cool it to below 120℃ at a cooling rate of 0.5-3℃ / min, and then let it cool naturally to room temperature to obtain the cured inductor preform.

10. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 9, characterized in that, The modified components also include silicon-based heat-resistant components, heat-resistant resin binders, curing agents, and lubricants. Between steps S3.1 and S3.2, the following is also included: A silicon-based heat-resistant component was added to silane-modified magnetic powder to construct a heat-resistant interface. The amount of silicon-based heat-resistant component added was 0.3–2.0 wt% of the phosphating magnetic powder. Ethanol and deionized water were added as hydrolysis dispersion media. The hydrolysis temperature was controlled at 40–70 °C, and the reaction time was controlled at 30–90 min. Then add heat-resistant resin binder, curing agent and lubricant and mix. The amount of heat-resistant resin binder added is 1.0 to 4.0 wt% of the mass of phosphated magnetic powder, the amount of curing agent added is 2 to 15 wt% of the mass of heat-resistant resin binder, and the amount of lubricant added is 0.1 to 0.8 wt% of the mass of phosphated magnetic powder. The mixing temperature is controlled at 60 to 90°C and the mixing time is controlled at 20 to 60 min.

11. The method for preparing an integrally molded inductor of iron-based nanocrystalline alloy powder according to claim 10, characterized in that, In step S3, the silane coupling agent includes at least one of aminosilane coupling agent, epoxysilane coupling agent, vinylsilane coupling agent, methacryloxysilane coupling agent, and mercaptosilane coupling agent; the silicon-based heat-resistant component includes at least one of silica sol, tetraethyl orthosilicate, and methyltriethoxysilane; the heat-resistant resin binder includes at least one of modified epoxy resin, silicone resin, phenolic resin, and polyimide precursor; the curing agent includes at least one of imidazole curing agent, acid anhydride curing agent, and phenolic curing agent; and the lubricant includes at least one of zinc stearate, calcium stearate, polyethylene wax, and paraffin wax.

12. An integrally molded inductor containing iron-based nanocrystalline alloy powder, characterized in that, It is manufactured by the method for preparing an integrally formed inductor of iron-based nanocrystalline alloy powder as described in any one of claims 1-11, wherein, α-Fe nanocrystals are used to reduce the magnetic loss of integrally molded inductors; Phosphate passivation solution is used to generate an insulating layer on the surface of ball-milled powder; Silane coupling agents are used to enhance the flowability of phosphating magnetic powder.

Citation Information

Patent Citations

  • Preparation method of nanocrystalline magnetic powder cores

    CN102744403A

  • Amorphous nanocrystalline soft magnetic particle, soft magnetic powder core, preparation method of amorphous nanocrystalline soft magnetic particle and soft magnetic powder core and electronic device

    CN117219390A